International law as social construct the struggle for global justice - Focarelli, Carlo (Oxford : Oxford University Press, 2012)
This title explores international law as a social construct by analysing its social foundations and by re-conceptualizing the way in which it is commonly understood. It asks what law is and how it works in society, and shows why it is worth to struggle for new and better-working rules in the international legal order.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: International law -- Interpretation and construction; Sociological jurisprudence